The Math Stack : Playing cards for math lovers - Stanciulescu, Diana, ....- (n.d. : Bolster Academy, 2015)
Mathematical constants and equations represent more than just numbers and are inherent in the hidden laws of the universe... mathematics is everywhere. The exquisite visual design of these playing cards enables an intuitive insight into the language of mathematics.
Keywords: Gezelschapsspel; Kaartspel; Mathematics; Strategisch Spel; Wiskunde